EcoHealth Center: reduce, reuse, recycle! - Sofia Monteiro; Maria João Nuno Lopes; Ana Paula Barata Coutinho (James Cook University, 2023)
Introduction: Climate change is a topic of growing interest and should guide our actions in society. Clinical practice must improve sustainability and ecological behavior as an opportunity. We intend to show how measures were implemented to reduce resource consumption in a health center in Gonçalo, a small village in the center of Portugal, with the support of local government spreading these practices across the community.Methods: The first step was to account for daily resource use in Gonçalo's Health Center. Opportunities for improvement were listed in a multidisciplinary team meeting and subsequently implemented. Local government was very cooperative in the implementation of such measures, helping us spread the intervention to the community.Results: A considerable reduction in resource consumption was verified, mainly the reduction of consumption of paper. Before this intervention, there was neither separation nor recycling of waste, which was initiated by this program. This change was implemented in the building of the Parish Council, at the Health Center and School Center of Gonçalo, where health education activities were promoted.Discussion: In a rural area, the health center is an integral part of the life of the community in which it operates. Thus, their behaviors have the power to influence that same community. By showing our interventions and through practical examples, we intend to influence other health units to be an agent for change within their communities. By reducing, reusing and recycling, we intend to be a role model.